2021
DOI: 10.1007/s40314-021-01729-7
|View full text |Cite
|
Sign up to set email alerts
|

Using a cubic B-spline method in conjunction with a one-step optimized hybrid block approach to solve nonlinear partial differential equations

Abstract: In this paper, we develop an optimized hybrid block method which is combined with a modified cubic B-spline method, for solving non-linear partial differential equations. In particular, it will be applied for solving three well-known problems, namely, the Burgers equation, Buckmaster equation and FitzHugh–Nagumo equation. Most of the developed methods in the literature for non-linear partial differential equations have not focused on optimizing the time step-size and a very small value must be considered to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Gu and others believe that in addition to the wide application of fractal, fractional differential equations developed from fractional calculus theory are also widely used in many fields such as physics, biology, engineering, finance, and even random walk [6]. Ramos and others found that for the diffusion equation with fractional order, the abnormal characteristic problems often appear in many problems can be well explained by it, such as abnormal transport process, gating dynamics of ion channels in some proteins, and application in cancer treatment [7]. Wang and others believe that fractional derivative has also been greatly applied and developed in delay differential equations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gu and others believe that in addition to the wide application of fractal, fractional differential equations developed from fractional calculus theory are also widely used in many fields such as physics, biology, engineering, finance, and even random walk [6]. Ramos and others found that for the diffusion equation with fractional order, the abnormal characteristic problems often appear in many problems can be well explained by it, such as abnormal transport process, gating dynamics of ion channels in some proteins, and application in cancer treatment [7]. Wang and others believe that fractional derivative has also been greatly applied and developed in delay differential equations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, these techniques are less expensive and have the ability to handle complex systems of equations. Parabolic PDEs have recently been solved using hybrid block methods [33,34]. The aim of this study is to present a scheme that combines DQM and a one-step hybrid block method, conserving mass and energy.…”
Section: Introductionmentioning
confidence: 99%
“…Finding a closed-form solution to this problem is difficult because of its considerable nonlinearity. As a result, several writers have suggested numerical approaches in the literature, such as the nonlinear self-adjoint method [28], the finite volume method [29], the B-spline collocation method [30], the cubic B-spline, and the cubic trigonometric B-spline collocation methods [31]. These techniques were created especially for the Buckmaster problem, a normal nonlinear equation.…”
Section: Introductionmentioning
confidence: 99%